P11.07 The spectrum of sexual behaviours among msm and associations with prevalent sexually transmitted infections and hiv. (13th September 2015) - Rice, CE; Norris, AH; Davis, JA; Lynch, CD; Fields, KS; Ervin, M; Turner, AN
Abstract : Introduction: "Sex" among men who have sex with men (MSM) encompasses a much broader range of behaviours than just anal intercourse, yet most sexual health research in this population focuses on only this one practice. We undertook this study to more fully characterise the spectrum of sexual behaviours endorsed by MSM seeking care in an urban, public STD clinic and the associations between these behaviours and prevalent STI and HIV. Methods: This cross-sectional study of 235 MSM was conducted from July 2012 through October 2013. Participants self-administered a standardised survey assessing several categories of sexual behaviour, including multiple types of receptive/insertive  behaviours, venues where sexual activity occurs, and sex while using drugs and alcohol. Men responded about behaviours over their lifetime and within the past three months. We generated unadjusted prevalence ratios (PRs) to characterise associations between recent participation in each behaviour and prevalent STI and HIV. Results: Participants' median age was 26 years. Most were white (57%) and employed (73%). Most, but not all, identified as gay (76%). One-third (35%) had rectal or urethral gonorrhoea or chlamydia, or primary/secondary syphilis. STI prevalence was significantly higher among men who reported using sex slings (PR: 2.04), anonymous sex (PR: 1.81), illicit drugs during sex (PR: 1.77), fisting (PR: 1.74), sex toys (PR: 1.44), and group sex (PR: 1.43). HIV prevalence was 17%, and was significantly higher among men who endorsed fisting (PR: 4.81), felching (PR: 3.92), enemas (PR: 4.04), sex slings (PR: 2.47), drug use during sex (PR: 1.98), and group sex (PR: 1.92). Conclusions: Many behaviours other than anal intercourse were significantly associated with prevalent STI and HIV in unadjusted analyses, demonstrating the need for prospective studies to examine causal relationships between specific behaviours and STI or HIV acquisition. Disclosure of interest statement: No authors have any conflict to disclose.